Menjaga Cinta di Tengah Perbedaan: Upaya Membangun Keharmonisan Keluarga dan Sosial dalam Pernikahan Beda Agama - Umam, Muhammad Sholahul (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2025)
Interfaith marriage in Indonesia presents complex challenges and opportunities for family harmony, shaped by Islamic, social, and normative perspectives. This article uses a descriptive qualitative research method with desk research data collection techniques. Legally, interfaith marriage faces significant obstacles due to conflicts between state and religious laws. This results in administrative difficulties and lack of official recognition, which can result in psychological distress and social stigma for couples and their families. Despite these challenges, many interfaith families report harmonious relationships, often achieved through adaptive, tolerant, and inclusive communication strategies that avoid religious conflict and emphasize shared values ​​such as kinship and mutual respect. Islamic legal perspectives generally prohibit interfaith marriage, although some scholars allow exceptions in certain circumstances. Debate continues over the interpretation of religious texts and the role of multiculturalism in legal reform. Socially, interfaith couples experience social and familial rejection, while some societies embrace pluralism and social harmony, suggesting that religious differences do not inherently affect family cohesion. These findings highlight the need for legal reform, improved public education, and psychological support to increase tolerance and protect the rights of interfaith families. The study suggests that communication, tolerance, and understanding between couples are key factors in reducing negative stigma toward interfaith couples, ultimately promoting harmonious coexistence in Indonesia’s diverse society.